L’autonomie : un concept central pour le développement de l’activité de travail des agriculteurs à l’ère de l’anthropocène - Xavier Coquil (Activités)
Farmers’ work activity in the Anthropocene era is very much in question: transform or disappear. Agricultural activity is extremely dependent on natural cycles and these are being strongly degraded by global changes. Self-determination and trust, critical thinking and political power are three dimensions of autonomy that are central to thinking about how to support the transformation of farmers’ activities. This transformation of activity is the result of a dual movement: emancipation from a normative, ultra-dominant and unsustainable socio-professional context, and the development of farmers’ work activity. Indeed, the dominant professional norms lead to a disconnection between agriculture and nature with very negative environmental effects. The challenge for farmers is to devise new ways of doing things and to think of their work in terms of a different pact with nature. Supporting farmers to become autonomous in all three dimensions enables them to take control of their conception of their work step by step. Designing their work requires them to gain confidence in themselves and to grasp political power in the bodies in which they build know-how and experiences of interest within this new framework of thought, in order to define a critical reflection on the artefacts they mobilize. The role, methods and postures of agricultural research, education and development are keenly examined so as to work on autonomy as a means. The transformations in farmers’ work activity are central to the sustainability of the agricultural sector.